2018
DOI: 10.1111/anu.12870
|View full text |Cite
|
Sign up to set email alerts
|

Optimum protein-to-lipid ratio requirement of the juvenile shi drum (Umbrina cirrosa) as estimated by nutritional and histological parameters

Abstract: The shi drum, Umbrina cirrosa, is considered quite promising candidate and emerging alternative Mediterranean aquaculture species to the dominant, European seabass, Dicentrarchus labrax, and gilthead seabream, Sparus aurata, due to its high growth rate and feed efficiency (Segato, Corato, Fasolato, & Andrighetto, 2005). Shi drum feeds mainly on invertebrates and fish (Abellan & Basurco, ), suggesting that this species has high protein requirements. Moreover, the shi drum has a good adaptation capacity to cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We speculate that there are significant differences in the nutritional requirements of Chinese sturgeon at different ages. Nutritional composition and ratio of diets play important roles in fish growth [28][29][30]. As the scale of artificial conservation of Chinese sturgeon continues to expand, quantity and quality of natural feed cannot be guaranteed, and an artificially formulated diet must be used.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that there are significant differences in the nutritional requirements of Chinese sturgeon at different ages. Nutritional composition and ratio of diets play important roles in fish growth [28][29][30]. As the scale of artificial conservation of Chinese sturgeon continues to expand, quantity and quality of natural feed cannot be guaranteed, and an artificially formulated diet must be used.…”
Section: Discussionmentioning
confidence: 99%
“…The results show a considerable improvement in villus height and width in P/E95 based on gut morphometry. The histomorphometry analysis of a recent work by Kokou et al [ 29 ] showed that the dietary protein-to-energy ratio affected intestinal health and ameliorated villus heights in juvenile shi drum. The ability of hybrid yellow catfish to digest their diets more effectively seems to be positively influenced by optimal dietary P/E ratios, improving their health, growth potential, and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid is deposited in vacuoles, which results in steatosis primarily in the liver, but it can also build up in enterocytes, as dietary lipid levels surpass the oxidation capability. There is evidence to support these effects on a wide variety of fish species, including juvenile shi drum ( Umbrina cirrosa ) and meagre ( Argyrosomus regius ) [ 29 , 30 ]. Hence, finding an ideal dietary protein-to-energy ratio is so essential to a fish's health and physiological condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic steatosis is common in fish fed with diets comprising high lipid (Kokou et al., 2019) or carbohydrates levels (Fernandes Junior et al., 2016), due to increased lipid deposition in the liver. Xie et al.…”
Section: Discussionmentioning
confidence: 99%